Dor cervical e qualidade de vida relacionada à saúde: estudo de base populacional - Maciel, Nicoly Machado (2017)
INTRODUCTION: The impact of neck pain in the general population has been associated with its influence on health-related quality of life (HRQoL) indicators. Studies indicate that individuals with cervical pain have worse mean scores in the physical and mental domains of HRQoL than those without pain. PURPOSE: To verify the association between the presence and severity of neck pain and Health-related quality of life in adults. METHODS: We conducted a population survey, through a complex sampling in two stages, totaling 600 participants in the urban area of Bauru, São Paulo. For data collection Interviews were conducted in households using the following instruments: 1. Characteristics of participants: demographic and socioeconomic aspects; 2. Nordic questionnaire for the analysis of musculoskeletal Symptoms; 3. Quality of Life: using the Medical Outcomes Study 36 - Item Short-Form Health Survey (SF-36). A descriptive, bivariate analysis was performed using the Pearson Chi-square test. For the comparison between the neck pain and painless individuals, Student's t-test and comparisons between age groups were used by means of Analysis of Variance, complemented with Tukey's test for paired comparisons. RESULTS: Women had a higher prevalence of neck pain than men in the last seven days and 12 months and had higher severity indexes; The mean HRQoL score was lower in both SF-36 domains in those who reported neck pain and those older than 60 years; The association of HRQoL to the index of severity of pain indicated that especially the physical domains had lower mean scores as the severity index increased. CONCLUSION: There was a significant association between HRQoL and neck pain; individuals with cervical pain had lower mean scores on the physical and mental dimensions of quality of life and, in the areas of Role Physical, Bodily Pain and Mental Health, individuals presented lower scores as the severity index increased